To rise again at a decent hour a novel - Ferris, Joshua 1974- (Penguin Books, 2014)
'There's nothing like a dental chair to remind a man that he's alone in the world, subject to pain, blood, decay, and a slow attenuation back down to the elements.' Paul O'Rourke - dentist extraordinaire, reluctant New Yorker, avowed atheist, disaffected Red Sox fan, and a connoisseur of the afternoon mochaccino - is a man out of touch with modern life. While his thriving dental practice occupies his days, his insomniac nights are filled with speculation and regret, as he ponders his mistakes with his ex-girlfriend (and receptionist) Connie, questions all the rituals that give his life meaning, and alternately marvels at and rails against the optimism and ignorance of the rest of humanity. So it goes, until someone begins to impersonate Paul online. Deeply committed to an analog life, Paul watches in impotent horror as a website, a Facebook page, and a Twitter account are created in his name to promote a little-known ancient religion. And yet what began as an outrageous violation of privacy soon becomes something far more soul-frightening: the possibility that the virtual 'Paul' might be a better version of the man in the flesh. Suddenly, everything Paul believes, or doesn't, seems to be at stake ... Joshua Ferris's dazzlingly inventive, brutally comic new novel cuts to the very heart of modern existence: the meaning of life, the certainty of death, and the importance of good oral hygiene
Keywords: Online identity theft / Fiction; Self-doubt / Fiction; Identity (Psychology) / Fiction; Psychological fiction